2020
DOI: 10.3390/insects11060369
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Decision Support Tools to Improve the Management of Root-Feeding Fly Pests of Vegetables in Western Europe

Abstract: Several important vegetable crops grown outdoors in temperate climates in Europe can be damaged by the root-feeding larvae of Diptera (Delia radicum, Delia floralis, Chamaepsila rosae, Delia platura, Delia florilega, Delia antiqua). Knowledge of pest insect phenology is a key component of any Integrated Pest Management (IPM) strategy, and this review considers the methods used to monitor and forecast the occurrence of root-feeding flies as a basis for decision-making by growers and the ways that such informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…As a consequence, crop losses can be as high as 100%, especially among young plants (Razinger et al, 2017). While some damage to roots may be tolerable for leaf or inflorescence vegetables such as cabbage or cauliflower, even slight damage can substantially reduce the quality of root vegetables like radish, turnip, or swede (Collier et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, crop losses can be as high as 100%, especially among young plants (Razinger et al, 2017). While some damage to roots may be tolerable for leaf or inflorescence vegetables such as cabbage or cauliflower, even slight damage can substantially reduce the quality of root vegetables like radish, turnip, or swede (Collier et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, stricter regulations due to environmental concerns as well as the development of insecticide resistance in D. radicum have reduced the availability of effective products worldwide (Joseph & Iudice, 2020; Shuhang et al, 2016). As a result of bans and restrictions on the use of relevant insecticides, reliable options for chemical control are lacking in several European countries (Collier et al, 2020; Herbst et al, 2017). With levels of plant resistance to D. radicum generally being too low in brassica crops, growers thus increasingly need to rely on physical, cultural and biological control strategies (Santolamazza‐Carbone et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Drepanosiphum platanoidis (Hemiptera: Aphididae) and Archips podanus (Lepidoptera: Tortricidae) each detected in one individual with a total of six reads for the former two species and 12 reads in the later. Chamaepsila rosae or carrot fly primarily affects crops such as carrots and parsnips (Collier et al 2020) and has been described as a major carrot pest within Europe (Szwejda and Wrzodak 2007).…”
Section: Ecosystem Servicesmentioning
confidence: 99%
“…Several decades of research into interactions between plants and arthropods have revealed that these organisms are involved in the struggle for survival, which is based on sophisticated mechanisms of perception, signaling, and defensive activation on the plant side and on effective suppression of defense mechanisms and chemical and behavioral adaptations on the arthropod side [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%